The role of genes domesticated from LTR retrotransposons and retroviruses in mammals - Kaneko-Ishino, Tomoko (Frontiers in Microbiology, 2012)
The acquisition of multiple genes from long terminal repeat (LTR) retrotransposons occurred in mammals. Genes belonging to a sushi-ichi-related retrotranspon homologues (SIRH) family emerged around the time of the establishment of two viviparous mammalian groups, marsupials and eutherians. These genes encode proteins that are homologous to a retrotransposon Gag capsid protein and sometimes also have a Pol-like region. We previously demonstrated that PEG10 (SIRH1) and PEG11/RTL1 (SIRH2) play essential but different roles in placental development. PEG10 is conserved in both the marsupials and the eutherians, while PEG11/RTL1 is a eutherian-specific gene, suggesting that these two domesticated genes were deeply involved in the evolution of mammals via the establishment of the viviparous reproduction system. In this review, we introduce the roles of PEG10 and PEG11 in mammalian development and evolution, and summarize the other genes domesticated from LTR retrotransposons and endogenous retroviruses (ERVs) in mammals. We also point out the importance of DNA methylation in inactivating and neutralizing the integrated retrotransposons and ERVs in the process of domestication.